(xsquare-2x)square-23(xsquare-2x)+120

Asked by Vidhi Srivastava | 27th Apr, 2013, 10:31: PM

Expert Answer:

let xsquare-2x = y
 
Hence, the equation becomes y^2 -23y + 120 =0
Using middle term splitting
 
 y^2 -15y-8y + 120 =0
(y-15) (y-8) =0
y = 15 or y = 8
Hence, x^2 -2x = 15 or x^2 -2x = 8
i.e.  x^2 -2x - 15 = 0 or x^2 -2x - 8 =0
Using middle term splitting again
(x-5)(x+3) = 0 or (x-4)(x+2) = 0
Hence, x = 5 or -3 or 4 or -2

Answered by  | 28th Apr, 2013, 10:10: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.